How to claim what is mine: Negotiating professional roles in inter-organizational projects - Bos -de Vos, Marina; Lieftink, Bente (A+BE | Architecture and the Built Environment, 2018)
Professional roles within inter-organizational projects have become increasingly diverse and contested, yet little is known about how the members of a profession react to the threats of marginalization these collaborative settings entail. Focusing on the architectural profession, in which historically established role boundaries have become particularly blurred, we analyse how professionals address the concept of these boundaries in order to negotiate their roles in inter-organizational projects. Drawing on empirical data from interviews with project architects, we identify and detail three types of boundary work: reinstating role boundaries, bending role boundaries, and pioneering role boundaries. These categories exemplify how professionals may frame the threat of marginalization differently depending upon their preconceptions of what constitutes professional work. This study provides important insights into how professionals reclaim, change, or temporarily adapt their practice domains in inter-organizational projects; how their boundary work practices help to (re)shape role structures; and how these practices may trigger different paths of professional evolution.